Pandangan Kantor Urusan Agama (KUA) Kecamatan Tanjung Pura Kabupaten Langkat tentang Hukum Mengqadha Sholat yang Ditinggalkan dengan Sengaja Karena Mengikuti Prosesi Adat Perkawinan (Studi Kasus Masyarakat Islam di Kecamatan Tanjung Pura Kabupaten Langka - Muhammad Haikal Syahputra; Ahmad Sanusi Luqman; Suaib Lubis (Journal Smart Law, 2024)
This research discusses the opinion of the Tanjung Pura District Office of Religious Affairs (KUA) regarding the law regarding brides making up for prayers that were intentionally left behind because they were following a traditional wedding procession. The research method used in this research is a descriptive qualitative research method with an empirical approach. The informants in this research were the Tanjung Pura District Religious Affairs Office (KUA), the bridal couple who were making up for the prayer, traditional leaders and the community. The research results explain. The form of the traditional Malay wedding procession in Tanjung Pura District uses the traditional Malay wedding procession which consists of many activities including: escorting the bride and groom, reciprocating rhymes, offering dances, barzanji marhaban, plain flour, eating before and exchanging halls and giving gifts. Factors that cause brides and grooms to take part in the traditional wedding procession in Tanjung Pura District include because it has become a tradition, has become a family agreement, has become the bride's dream and so that the wedding party becomes more lively. The factors that cause the bride and groom to abandon their prayers are that the bride and groom are busy following a very long traditional procession, as well as knick-knacks that are difficult to remove and wear a second time for the reason of maintaining good manners when at the wedding they are not allowed to go anywhere. Ilat) to make up prayers. The opinion of the Tanjung Pura District Office of Religious Affairs (KUA) is that making up the prayer for the bride and groom who carry out the traditional Malay wedding procession is not legalized because carrying out the traditional marriage procession does not receive a rukhsah because the qadha prayer is a rukhsah, where the rukhsah is a relief or way. the exit that Allah gives someone in certain conditions such as sleeping, war, travel, illness and so on.